Value judgements in the decision-making process for the elderly patient - Ubachs-Moust, J. (Journal of medical ethics, 2008)
The question of whether old age should or should not play a role in medical decision-making for the elderly patient is regularly debated in ethics and medicine. In this paper we investigate exactly how age influences the decision-making process. To explore the normative argumentation in the decisions regarding an elderly patient we make use of the argumentation model advanced by Toulmin. By expanding the model in order to identify normative components in the argumentation process it is possible to analyse the way that age-related value judgements influence the medical decision-making process. We apply the model to practice descriptions made by medical students after they had attended consultations and meetings in medical practice during their clinical training. Our results show the pervasive character of age-related value judgements. They influence the physician’s decision in several ways and at several points in the decision-making process. Such explicit value judgements were not exclusively used for arguments against further diagnosis or treatment of older patients. We found no systematic “ageist” pattern in the clinical decisions by physicians. Since age plays such an important, yet hidden role in the medical decision-making process, we make a plea for revealing such normative argumentation in order to gain transparency and accountability in this process. An explicit deliberative approach will make the medical decision-making process more transparent and improve the physician-patient relationship, creating confidence and trust, which are at the heart of medical practice.